Overview of the African Human Rights and Justice System - Barigayomwe, Rogers (East African Nature and Science Organization, 2025)
This thesis examines the African Human Rights and Justice System, focusing on the mechanisms established to promote and protect human rights on the continent. It provides a comprehensive overview of the African Charter on Human and Peoples’ Rights (ACHPR), which represents the foundational legal framework for human rights in Africa. The research details the roles of the African Commission on Human and Peoples’ Rights and the African Court on Human and Peoples’ Rights, exploring their functions, challenges, and the impact of their actions on human rights protections. The research methodology was a qualitative analysis of legal documents, case studies, and reports from human rights organizations, this study identifies significant gaps in enforcement mechanisms and the implementation of human rights laws. Moreover, the thesis highlights the historical context of human rights in Africa, emphasizing the effects of colonialism and the need for a concerted effort to eradicate its remnants for genuine human rights realization. The findings suggest that while substantial frameworks exist, effective operationalization remains hindered by political, social, and economic factors. The study concludes with recommendations for strengthening the African Human Rights and Justice System, including enhancing the capacity of the existing institutions, fostering greater accountability, and encouraging civil society participation. This research contributes to the ongoing discourse on human rights in Africa and aims to provide a foundation for future reforms in the regional justice system